Cost efectivenss of harm reduction : HIV / Sharifah Fadzlon Abdul Hamid ... [et al.] - Abdul Hamid, Sharifah Fadzlon; Omar, Normah; Sulaiman, Suzana; Wee, Shu Hui; Md Fatah, Nurshahidah; Mohd Zan, Nurhazeera (Research Management Institute (RMI), 2013)
Recent years have seen increasing cases of intravenous drug users (IDUs) not only in Malaysia but also worldwide and its consequential negative impact upon society, one of which is the rising cases of HIVs. Recognising that it is impossible to eradicate HIVs, many countries embark on harm reduction programmes. The programmes include the syringe exchange programmes (NSEP) and the methadone maintenance therapy (MMT). Drug trafficking being a lucrative business has lead to the increase in the supply of illicit drugs and thus increase the number of drug addicts globally and Malaysia is no exception. Every year many countries spent a large sum of money to tackle the problem associated with illicit drug. In Malaysia many of the drug users are below the age of 40 years and they are mainly IDUs. Transmission of HIV is found largely among IDUs. The International Harm Reduction Association (ihra) defined harm reduction as practices that aim primarily to reduce the adverse health, social and economic consequences of the use of legal and illegal psychoactive drugs without necessarily reducing drug consumption.